Didática em cursos de licenciatura: concepções de docentes e perspectivas na formação de professores - Rosa, Luana Bastos do Nascimento (2022)
This study analyzes questions relational with the Didactic subject in the context of courses for teaching, putting in discussion the role that this area of knowledge assumes in the process of teacher’s qualification. It is also discussed the problematisation of teaching staff conceptions, making an intersection with reflections about this field of knowledge and the teacher staff of college education. As a problematization, tries to answer the following questions: what is role of the Didactic in the teacher’s qualification based on the contemporary debate in this area in Brazil? What conceptions the teachers who teach this subject in graduation courses have as for the contribution of Didactic in the future teachers formation? The theory used in this research underlies in recent Critic Didactic’s surveys, referenced published productions about the theme in the last few years. As main references, the research interact with: Almeida (2019), Candau (1997, 2020), Faria (2011, 2014, 2016, 2018, 2020, 2021), Franco (2013, 2014, 2019), Marin (2005, 2012, 2020), Pimenta (2012, 2015, 2018, 2019, 2020), Pimenta e Anastasiou (2014), Pontes (2020), Saviani (1991), Torres (2014), Veiga (1991, 2004) e Veiga e Silva (2021). The methodology adopted referred to research in qualitative character which rely on analysis of bibliographic sources and application of an online survey form structured with open-ended questions sent to ten people from the teaching staff who teach the Didactic subject in licentiate courses at Universidade Federal do Espírito Santo. As results, is identified, regarding the discussion in the Didactic studies, two important considerations: a) the devalorization of the subject as a component in the course program result in lack of own knowledge in Didactic undermining the future qualification of teachers; b) the difficult of articulation in the area with contents happens because of teachers who do not know the main epistemological object of Didactics reflecting the absence of preparation who teaches the subjects. With regard to the data of the field survey, stands out that the participants identify the Didactic subject is compromised with the teacher qualification, because contribute with formative dialogues to the praxis reflection e to think critically the elements which structure the process of teaching-learning. In relation with the data of the field research was identified the following categories of discussion: Didacti and praxis; Didactic and dialogue; Didactic and “what to do”; Structural elements do Didactic; The teacher as a researcher; and The Knowledge of the teacher. Is highlighted that the Didactic subject is known as the area of knowlegde and main course in the teacher’s qualification, since that the participants indentify that the subject is compromised with the teacher’s formation, because contributes with realization of formative dialogues for the reflection about the praxis of the teachers and to think critically the elements which structure the process of teaching-knowledge.The participants reinforce the contribution of Critic Didactic in the promotion of possibilities to the teacher who ministers the Didactic subject and also to make the student reflect about what to do in the school education, considering that the subject provides knowledge about teaching in the basic education, problematize and study the scenarios and educational process by the concept of researcher teacher.